The Economic Stimulus Package to Boost Malaysia Property Market (Post COVID-19) - Nawi, Abdol Samad; Alias, Mohd Azuan Mohd; Mat, Mustafa Kamal; Hasan, Zakiyah; Zulkarnain, Siti Hafsah (Journal Of Management Analytical and Solution (JoMAS), 2023)
The purpose of this study was to see how the Economic Stimulus Package impacted the Malaysia property market. The impact of the Overnight Policy Rate (OPR) on the property market was studied as a case study. The data wasÂ  analyzed using the Ordinary Least Squares method (OLS) and covered the years 2010Â  to 2020. It was discovered that OPR has a positive sign in relation the property market, and the Granger Causality Test demonstrates that OPR causes the volume of transactions in the property market. According to the study, the government should continue to provide the essential stimulus package to boost growth in the Malaysia Property Market